Physical Activity and Obesity: Biomechanical and Physiological Key Concepts - Julie Nantel; Marie-Eve Mathieu; François Prince (Journal of Obesity)
Overweight (OW) and obesity (OB) are often associated with low levels of physical activity. Physical activity is recommended to reduce excess body weight, prevent body weight regain, and decrease the subsequent risks of developing metabolic and orthopedic conditions. However, the impact of OW and OB on motor function and daily living activities must be taken into account. OW and OB are associated with musculoskeletal structure changes, decreased mobility, modification of the gait pattern, and changes in the absolute and relative energy expenditures for a given activity. While changes in the gait pattern have been reported at the ankle, knee, and hip, modifications at the knee level might be the most challenging for articular integrity. This review of the literature combines concepts and aims to provide insights into the prescription of physical activity for this population. Topics covered include the repercussions of OW and OB on biomechanical and physiological responses associated with the musculoskeletal system and daily physical activity. Special attention is given to the effect of OW and OB in youth during postural (standing) and various locomotor (walking, running, and cycling) activities.